Magnetically‐actuated microcages for cells entrapment, fabricated by laser direct writing via two photon polymerization - Popescu, Roxana Cristina; Calin, Bogdan Stefanita; Tanasa, Eugenia; Vasile, Eugeniu; Mihailescu, Mona; Paun, Irina Alexandra (Frontiers in Bioengineering and Biotechnology, 2023)
The manipulation of biological materials at cellular level constitutes a sine qua non and provocative research area regarding the development of micro/nano‐medicine. In this study, we report on 3D superparamagnetic microcage‐like structures that, in conjunction with an externally applied static magnetic field, were highly efficient in entrapping cells. The microcage‐like structures were fabricated using Laser Direct Writing via Two‐Photon Polymerization (LDW via TPP) of IP‐L780 biocompatible photopolymer/iron oxide superparamagnetic nanoparticles (MNPs) composite. The unique properties of LDW via TPP technique enabled the reproduction of the complex architecture of the 3D structures, with a very high accuracy i.e., about 90 nm lateral resolution. 3D hyperspectral microscopy was employed to investigate the structural and compositional characteristics of the microcage‐like structures. Scanning Electron Microscopy coupled with Energy Dispersive X‐Ray Spectroscopy was used to prove the unique features regarding the morphology and the functionality of the 3D structures seeded with MG‐63 osteoblast‐like cells. Comparative studies were made on microcage‐like structures made of IP‐L780 photopolymer alone (i.e., without superparamagnetic properties). We found that the cell‐seeded structures made by IP‐L780/MNPs composite actuated by static magnetic fields of 1.3 T were 13.66 ± 5.11 folds (p < 0.01) more efficient in terms of cells entrapment than the structures made by IP‐L780 photopolymer alone (i.e., that could not be actuated magnetically). The unique 3D architecture of the microcage‐like superparamagnetic structures and their actuation by external static magnetic fields acted in synergy for entrapping osteoblast‐like cells, showing a significant potential for bone tissue engineering applications.